Inclusion of essential oils in a calf milk replacer and their effects on growth performance and the immune and oxidative systems - Nora L.* (2024)
© The Author(s), under exclusive licence to Springer-Verlag London Ltd., part of Springer Nature 2024.The use of essential oils in animal feed is increasing, but it needs to be applicable. This study determined whether a reformulated milk replacer containing a blend of essential oils composed of cinnamon, oregano, and eucalyptus improves suckling calves’ immune and oxidative systems, consequently improving productive performance. Sixteen Holstein calves (ten days old) suckled for 60 days. The animals were divided into a control group (n = 8), which received the commercial milk replacer, and a treatment group (n = 8), which received a milk replacer containing oils. The animals were fed twice daily with 0.25 kg of milk replacer diluted in two liters of water at each feeding. The milk replacer in the treatment group contained 5 g of additive per kg. The milk replacer containing essential oils had a strong aroma and odor and consequently was rejected by two calves in the treatment group. These animals were withdrawn from the experiment after five days of attempting to adapt them. The calves also received pelleted concentrate from the beginning of the experiment and chopped hay from 28 days onwards (both ad libitum). The treatment group showed more weight gain and feed efficiency than control animals. Lower lymphocyte counts were observed in calves fed milk replacers containing essential oils. Total serum protein was higher due to increased globulins in calves in the treatment group than in the control group. Serum immunoglobulin A and heavy-chain immunoglobulins were higher in the treatment group. Lower levels of lipid peroxidation and higher total antioxidants were observed in the serum of calves in the treatment group. We conclude that some animals may not adapt to the milk replacer containing essential oils due to the odor; however, the calves that consumed the milk containing the essential oils showed stimulated humoral immune responses that minimized the physiological oxidative stress of the rearing phase and consequently favored growth and weight gain.